2019
DOI: 10.1101/805838
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How beat perception coopts motor neurophysiology

Abstract: A fundamental aspect of music cognition is the perception of an underlying metronome-like pulse ("the beat") in complex rhythmic patterns. A key finding from neuroimaging is that even in the absence of movement, beat perception strongly engages the motor system. Existing efforts to create conceptual and computational models of beat perception do not strongly engage with known neurocomputational properties of the motor system. Here we construct a mechanistic model of beat perception grounded in neurophysiology.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 138 publications
0
12
0
Order By: Relevance
“…It is interesting that cortical spiking timescales are sensitive to a stimulus feature that is approximately 40 3 slower than the timescale itself (800 ms versus 20 ms), which suggests that A1 regular-spiking unit timescale dynamics are likely the product of other local or long-range circuits that respond more directly to the change in predictable stimulus timing. 27 Prior work has shown that the temporal decay of sensory-evoked spikes can be regulated by recurrent local circuits and inter-regional feedback loops. 6,7,[28][29][30][31] Cortical GABAergic neurons that express somatostatin or neuron-derived neurotrophic factor are clear candidates to dampen principal neuron spiking timing because they target the distal dendrites of A1 pyramidal neurons to regulate network excitability and recurrent excitation, but are also sensitive to slowly changing internal state variables.…”
Section: Spike Rate Adaptation Versus Spike Timescale Dynamicsmentioning
confidence: 99%
“…It is interesting that cortical spiking timescales are sensitive to a stimulus feature that is approximately 40 3 slower than the timescale itself (800 ms versus 20 ms), which suggests that A1 regular-spiking unit timescale dynamics are likely the product of other local or long-range circuits that respond more directly to the change in predictable stimulus timing. 27 Prior work has shown that the temporal decay of sensory-evoked spikes can be regulated by recurrent local circuits and inter-regional feedback loops. 6,7,[28][29][30][31] Cortical GABAergic neurons that express somatostatin or neuron-derived neurotrophic factor are clear candidates to dampen principal neuron spiking timing because they target the distal dendrites of A1 pyramidal neurons to regulate network excitability and recurrent excitation, but are also sensitive to slowly changing internal state variables.…”
Section: Spike Rate Adaptation Versus Spike Timescale Dynamicsmentioning
confidence: 99%
“…Though PIPPET and PATIPPET are not committed to a particular brain-based implementation, advances in the brain basis of timing and beat-keeping combined with the hypothesized neural bases of predictive processing suggest the beginnings of a plausible implementation of PIPPET in the brain. A detailed discussion of a possible neural basis of beat maintenance is presented in [63]. Briefly, supplementary motor area may maintain an ongoing estimate of mean phase through some combination of intrinsic dynamics and interaction with the basal ganglia, while dopaminergic signaling in striatum may maintain an estimate of phase uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments with non-human primates have shown neural trajectories in medial premotor cortex (MPC, encompassing the supplementary and pre-supplementary motor areas) that represent progress through self-generated behavioral processes. The author hypothesizes in [76] that similar trajectories represent rhythmic phase in human MPC. A representation of a linear phase ϕ , used in the phase inference framework for flexibility and mathematical tractability, would seem to be a limiting factor for implementation in the brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas it is commonly hypothesized that motor commands lead to better prediction of sensory inputs and thus benefit individual's adaptability to its environment (Wolpert et al, 1995;Schubotz, 2007;Schroeder et al, 2010;Cannon and Patel, 2020), the advantage of such a mechanism is not as clear during imagery, in which the sensory information had ostensibly already been established and can be retrieved at will. Nevertheless, the undeniable gap between stored knowledge and its transient representation in conscious experience could perhaps be somewhat mitigated by this mechanism.…”
Section: The Effect Of Rhythmic Movement On the Representation Of Imamentioning
confidence: 99%